An Ionic Liquid Consisting of Crown Ether – Coordinated Hydronium Cation and Amide Anion. (30th August 2016) - Takeoka, Shun; Kitada, Atsushi; Fukami, Kazuhiro; Murase, Kuniaki
Abstract : We first report an ionic liquid (IL) that consists of hydronium (H3 O + ) ion encapsulated by 18–crown–6–ether (18C6) and an amide anion. The composition of the crown ether–coordinated hydronium amide IL was estimated to be as [H3 O + 18C6][Tf2 N – ]. The presence of H3 O + was revealed from the characteristic bands of the hydronium ion present in the infrared spectra. The melting point of [H3 O + 18C6][Tf2 N – ] was 68–70 °C. At 70 °C, the viscosity of [H3 O + 18C6][Tf2 N – ] was 39.5 mPa s, the conductivity was 1.9 mS cm –1, and the density was about 1.32 g cm –3 . These bath properties of [H3 O + 18C6][Tf2 N – ] were similar to those of common ILs at room temperature.